Type 1 Tympanoplasty- Impact of Perforation Size and Site on Closure and Audiological Improvement - Dr. Ankit Singla (International Journal of Medical Science And Diagnosis Research, 2018)
Introduction: Tympanoplasty is the procedure of choice for the management of Chronic Suppurative Otitis Media of Tubotympanic type. Methods: Type 1 Tympanoplasty was done in 100 cases of chronic suppurative otitis media (safe type) by underlay technique using temporalis fascia graft via postaural or permeatal approach. All the patients fulfilled the accepted criteria for tympanoplasty. Results and interpretation: The successful closure of tympanic membrane perforation was higher in medium (94.33%) & small perforations (89.28%) than the larger perforations (78.94%). However the success percent was not statistically significant. The successful closure of tympanic membrane perforation was 100% in case of posterior placed perforations and was also relatively high in central perforations (90.27%) than the anterior perforations (75%). However this difference in tympanic membrane closure success based on site of perforation was also statistically insignificant. The success rate with post auricular approach (91.46%) was not statistically different from the success rate with the permeatal approach (83.33%). The success rate in smokers (66.66%) was significantly lower than in non-smokers (96.20%). Postoperative patients showed significant improvement in hearing following successful closure of tympanic membrane perforation. Larger perforations have more audiological gain than medium and small sized perforations also showed more audiological gain for central and posterior perforations than anterior perforations. No otitis media or iatrogenic sensorineural hearing loss in a follow-up of three months. Conclusion: Follow-up of the cases was done at 6 weeks and 12 weeks after operation. The overall success rate for graft take up was 90% at the end of 3 months of follow-up. Keywords: Chronic Suppurative Otitis Media, sensorineural hearing loss, Tympanoplasty, tympanic membrane perforation, temporalis fascia graft.